Longitudinal Study of Individual Exercises in Elite Rhythmic Gymnastics - Sierra-Palmeiro, Elena; Bobo-Arce, Marta; Pérez-Ferreirós, Alexandra; Fernández-Villarino, María A. (Frontiers in Psychology, 2019)
The performance evolution in rhythmic gymnastics depends on changes in code of points. At the beginning of each Olympic Cycle the code of points changes and therefore, the content of the competition exercises, as well. This study aimed to analyse –for each apparatus– the evolution of number of technical elements and final score over the last two decades (last 13 world championships), how they have been affected by changed code of points, and how the final score relates to the number of technical elements performed. The sample consisted of 416 exercises in five apparatus: ball (96), rope (40), hoop (96), ribbon (88), and clubs (96). The following variables were gathered: code of points, apparatus, technical group, total number of elements, final classification, and final score. Linear mixed-effects models were used to examine the effects on the number of elements and final score in each apparatus. The number of technical elements increased in all apparatus, between 7.4 and 20 % over a ten-year period. There were mixed evolutions of final score between the different apparatus, between -6.3 and 14 % over a ten-year period. There is small increase in number of elements in hoop and a small decrease in rope after a code change. There was a small decrease in final score in championships after a code change in hoop, moderate in clubs and ribbon, and large in rope. There was a negative relationship between number of elements performed and final score in clubs. In conclusion, the code change generally effects the final score negatively, but there were apparatus specific effects of code change on number of elements and relationship between number of elements and final score.